Influence of Continuous Physiologic Hyperinsulinemia on Glucose Kinetics and Counterregulatory Hormones in Normal and Diabetic Humans - Saccà, Luigi (1979)
The effects of continuous infusions of insulin in physiologic doses on glucose kinetics and circulating counterregulatory hormones (epinephrine, norepinephrine, glucagon, cortisol, and growth hormone) were determined in normal subjects and diabetics. The normals received insulin at two dose levels (0.4 and 0.25 mU/kg per min) and the diabetics received the higher dose (0.4 mU/kg per min) only. In all three groups of studies, continuous infusion of insulin resulted in an initial decline in plasma glucose followed by stabilization after 60-180 min. In the normal subjects, with the higher insulin dose there was a fivefold rise in plasma insulin. Plasma glucose fell at a rate of 0.73±0.12 mg/min for 45 min and then stabilized at 55±3 mg/dl after 60 min. The initial decline in plasma glucose was a result of a rapid, 27% fall in glucose output and a 33% rise in glucose uptake. Subsequent stabilization was a result of a return of glucose output and uptake to basal levels. The rebound increment in glucose output was significant (P < 0.05) by 30 min after initiation of the insulin infusion and preceded, by 30-45 min, a significant rise in circulating counterregulatory hormones. With the lower insulin infusion dose, plasma insulin rose two- to threefold, plasma glucose initially fell at a rate of 0.37±0.04 mg/min for 75 min and stabilized at 67±3 mg/dl after 75 min. The changes in plasma glucose were entirely a result of a fall in glucose output and subsequent return to base line, whereas glucose uptake remained unchanged. Plasma levels of counterregulatory hormones showed no change from basal throughout the insulin infusion. In the diabetic group (plasma glucose levels 227±7 mg/dl in the basal state), the initial rate of decline in plasma glucose (1.01±0.15 mg/dl) and the plateau concentration of plasma glucose (59±5 mg/dl) were comparable to controls receiving the same insulin dose. However, the initial fall in plasma glucose was almost entirely a result of suppression of glucose output, which showed a twofold greater decline (60±6%) than in controls (27±5%, P <0.01) and remained suppressed throughout the insulin infusion. In contrast, the late stabilization in plasma glucose was a result of a fall in glucose uptake to values 50% below basal (P < 0.001) and 39% below that observed in controls at termination of the insulin infusion (P < 0.01). Plasma norepinephrine and glucagon failed to rise during the insulin infusion, whereas plasma epinephrine, cortisol, and growth hormone rose to values comparable to controls receiving the same insulin dose. It is concluded that (a) in normal and diabetic subjects, physiologic hyperinsulinemia results in an initial decline followed by stabilization of plasma glucose despite ongoing infusion of insulin; (b) in the normal subjects, a rebound increase in glucose output is the initial or principal mechanism counteracting the fall in plasma glucose and occurs (with an insulin dose of 0.25 mU/kg per min) in the absence of a rise in circulating counterregulatory hormones; (c) in diabetics, although the changes in plasma glucose are comparable to controls, the initial decline is a result of an exaggerated suppression of glucose output, whereas the stabilization of plasma glucose occurs primarily as a consequence of an exaggerated fall in glucose uptake; and (d) failure of plasma norepinephrine as well as glucagon to rise in the diabetics may contribute to the exaggerated suppression of glucose output.